Microencapsulation of a palm oil-based alkyd by amino resins for self-healing application / Nurshafiza Shahabudin - Nurshafiza , Shahabudin (2016)
The failure of many structural polymers usually begins from the micro-cracks formed within the materials. Materials which contain healing agents (in microcapsules) can autonomously repair these cracks to prevent further propagation and failure. When cracks occur and rupture the microcapsules, the healing agent released would solidify through selected mechanism. In this work, a potential healing material was developed using an alkyd from palm kernel oil (PKO). The alkyd was synthesized to have a controlled amount of carboxylic groups (COOH), capable to form crosslinking reaction with the epoxide groups in the epoxy matrix. The alkyd was encapsulated into poly(urea-formaldehyde) (PUF) and poly(melamine-urea-formaldehyde) (PMUF) resins forming the microcapsules, which were embedded into an epoxy matrix. The functional groups of alkyd and shell materials in the microcapsules were confirmed by the appearance of the respective characteristic peaks using attenuated total reflectance-Fourier transform infrared (ATR-FTIR). Differential scanning calorimetry (DSC) analysis of the microcapsules showed a glass transition (Tg) around −12° C due to the alkyd and sharp melting temperature (Tm) at 148°C and 192°C due to the PUF and PMUF shells respectively. Another broad Tm at 0−15°C was attributed to the alkyd core. Thermogravimetric analysis (TGA) revealed that the PUF and PMUF microcapsules were thermally stable up to 250°C and 260°C, respectively. Field emission scanning electron microscopy (FESEM) examination of the broken shell of the microcapsules showed a smooth inner surface and a rough outer surface. The outer surface consisted of layered structures formed by PUF and PMUF nanoparticles. The microcapsules mix readily into the epoxy and were found to disperse well in the matrix as revealed by images in optical microscope and FESEM. Microcapsules of 1−3 wt. % could be incorporated into an epoxy matrix without noticeably affecting the flexural strength and micro-indentation hardness. To demonstrate the plausible healing reaction between the alkyd and the epoxy, a small amount of the amine hardener was replaced with the alkyd in the epoxy formulation. Curing was carried out at room temperature for 24 h and 100°C for 2 h and the blends hardened readily.